(Plasmonic gold core)@(ultrathin ruthenium shell) nanostructures as antenna-reactor photocatalysts toward nitrogen photofixation. Issue 7 (24th December 2021) - Jia, Henglei; Yang, Yuanyuan; Dou, Yanrong; Li, Fan; Zhao, Mengxuan; Zhang, Chun-yang
Abstract : We develop an antenna-reactor plasmonic photocatalyst for nitrogen photofixation by precisely tailoring the ultrathin ruthenium shell on gold nanorods. Abstract : Ruthenium (Ru) is known as the optimal metal catalyst for ammonia (NH3 ) synthesis, but the poor light-harvesting capability restricts its application in photocatalysis. Herein, we construct an antenna-reactor nanostructure through the controllable growth of an ultrathin Ru nanocluster shell with desired catalytic activity on the plasmonic gold (Au) nanoantennas. In this nanostructure, Au nanoantennas interact strongly with light to generate hot carriers, meanwhile Ru nanoclusters adsorb and activate N2, leading to the reduction of N2 to NH3 by the generated hot electrons. This antenna-reactor plasmonic photocatalyst exhibits shell-thickness-dependent photocatalytic activity toward nitrogen (N2 ) photofixation under visible and near-infrared light illumination.